An assessment of pensim2 - Carl Emmerson; Howard Reed; Andrew Shephard (Institute for Fiscal Studies (IFS), 2004)
The Department for Work and Pensions (DWP)'s Pensim2 model is a dynamic microsimulation model. The principal purpose of this model is to estimate the future distribution of pensioner incomes, thus enabling analysis of the distributional effects of proposed changes to pension policy. This paper presents the results of an assessment of Pensim2 by researchers at the IFS. We start by looking at the overall structure of the model, and how it compares with other dynamic policy analysis models across the world. We make recommendations at this stage as to how the overall modelling strategy could be improved. We then go on to analyse the characteristics of most of the individual modules which make up Pensim2, examining the data used and the regression and predictions used in each step. The results from this examination are used to formulate a set of short and medium-term recommendations for developing and improving the model. Finally, we look at what might become possible for the model over a much longer time frame – looking towards developing a `Pensim3' model over the next decade or so.
Keywords: H55; 330; Pensions; microsimulation; policy analysis; Simulation; Alterssicherung; Kritik